STUDI KINETIKA DEGRADASI LIMBAH ALKILBENZEN SULFONAT (ABS) DENGAN PROSES ELEKTRO FENTON - Rif'an Fathoni; Purwanto Purwanto (Universitas Mulawarman, 2022)
This study describes the effect of operating conditions such as weight ratio (H2O2/COD), the initial pH of waste and molar ratio fenton reagent (H2O2/Fe2+) to the degradation of waste alkylbenzene sulfonate (ABS). The degradation of ABS with the Electro Fenton process (E-Fenton) conducted in a laboratory scale batch reactor. The increasing doses of the weight ratio the production of hydroxil radicals will be increase and of course will increase the rate of organic degradation. Using a weight ratio that exceeds the theoretical calculations tend to decrease the degradation of ABS concentration. The weight ratio of 2,1 resulted in a decrease of ABS concentration, COD and BOD5 of 94,075%, 94,040%, 81,273%, respectively. Medium acidity (pH) is one of the most decisive factor of Electro-Fenton process, at a pH 3 yield degradation of ABS amounted 98,093%. ABS removal efficiency increased with the increase of ferrous ion dosage at fenton’s reagent molar ratio and reached highest of ABS concentration, COD and BOD5 of 99,05%, 96,64%, and 91,18%, respectively, for the operating time for 60 minutes. A kinetic study was carried out using first order reaction kinetics model. Temperature changes that occur when the research generates activation energy of 80,811 J/K.mol through the Arrhenius equation. Keywords: alkylbenzene sulfonat, arrhenius, electro fenton, fenton reagent, kinetic study